(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the significance of right ventricular dysfunction in patients suffering from coronary artery disease. Study Design: Observational study. Place and Duration of Study: This study was conducted at Karachi Institute of Heart Diseases and Dow University Hospital OJHA Campus Karachi from 1st March 2017 to 31st August 2017. Materials and Methods: A total of 561 patients with documented CAD matched our inclusion criteria. Patients with congenital heart defects, valvular heart diseases or those with any surgical intervention were excluded. Following parameters were measured on echocardiography: ejection fraction, two-dimensional size assessment and TAPSE.” Results: It includes 381 (70%) males and 180 (30%) females. The mean age of patients was found to be 54.3 + 11.4 years. Mean age of female patients was found to be 56.5 + 7.8 years and those of male patients is 51.5 + 12.3 years Mean right ventricular ejection fraction was found to be 42.7% + 6.7%. In male patients the mean RV ejection fraction was 43.61 ± 8.11% as compared to 39.32 ± 9.14% in female patients (p=0.432). According to TAPSE measurements right ventricular dysfunction was present in 26.5% (n=149) patients. Statistically significant differences were found between RV ejection fractions of females and males with 23% and 29.6% patients respectively (p=0.021). 31.5% of patients having right ventricular dysfunction had a previous history of myocardial infarction.” Conclusion: There is moderate prevalence of right ventricular dysfunction in patients with CAD. It should be assessed and treated at the earliest for better outcomes. Further studies should be carried out on large scales in all patients with CAD.”